PERSEPSI DOSEN UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARI TERHADAP PRODUK MAKANAN BERLABEL HALAL - Iman Setya Budi; Parman Komarudin (STAI Syubbanul Wathon Magelang, 2020)
In Islamic teachings, a Muslim is taught to eat halal food. Islam prohibits the consumption of pork, alcohol, blood, dead meat, and meat that is not slaughtered according to Islamic law. The absence of a label on a product will make Muslim consumers careful in deciding the consumption of these products. The halal label on product packaging in Indonesia is a logo composed of Arabic letters that form the word halal in a circle. Thus, consumers can get a little information that can help them determine the halalness of a product for themselves. This study aims to determine the perceptions of the Kalimantan Islamic University Lecturer Muhammad Arsyad Al Banjari (UNISKA MAB) on food products labeled as Halal. This study used the descriptive qualitative method. In collecting data using observation techniques, questionnaires, and documentation. The research subjects were 50 lecturers at the Islamic University of Kalimantan Muhammad Arsyad Al Banjari (UNISKA MAB). The results of this study indicate that the perception of a lecturer at the Islamic University of Kalimantan Muhammad Arsyad Al Banjari (UNISKA MAB) on food products labeled as halal with a percentage level of 53% strongly agrees or is important in choosing products and halal labels to be a consideration for product purchasing decisions with a percentage level of 72.34 %.